The effect of Cr doped in amorphous carbon films on electrical conductivity: Characterization and mechanism. (1st September 2021) - Hou, Kun; Yi, Peiyun; Li, Xiaobo; Peng, Linfa; Lai, Xinmin
Abstract: Metallic bipolar plates (BPPs) are prospective candidates for BPPs in PEMFCs due to their lower cost and higher power density than traditional graphite. Coatings are used to enhance the electrical conductivity and anti-corrsive quality of BPPs, and amorphous carbon (a-C) films have attracted broad attentions from both industry and academia. In this study chromium was incorporated into a-C to further enhance conductivity. A series of Cr-doped a-C films (a-C:Cr) with different doping contents were prepared by CFUBMSIP. Moreover, Microstructure analyses and composition characterizations were performed to explore the mechanism. The results show that Cr decreases the interfacial resistance with satisfying the anti-corrosive behavior. XRD patterns indicate that Cr will form chromium carbide phase and pure metal phase. Moreover, TEM results also show that Cr atoms bond with C atoms. SEM photographs show that Cr atoms refine the grain size and compact the film all the same. C 1s spectrum of XPS shows that C-sp 2 /C-sp 3 increases first and then decreases, reaching the maximum level of 1.708 at Cr0.205, indicating the resistance drops first and then increases. In addition, Cr doping will also bring changes in nano-hardness and surface roughness. Graphical abstract: (a) Interfacial contact resistance and contact resistance of samples series, indicating the mechanism of interfacial contact resistance differs from that of contact resistance; (b) Bulk resistance of samples series, indicating resistance in-plane differ from resistance through –plane; (c) Potentiodynamic polarization curves of samples series, indicating anti-corrosive behavior increase first then decrease as the doping content increases; (d) Raman results of samples series, indicating Cr's incorporation would change the micro-structure of a-C phase of the coatings. Image 1 Highlights: The regular and principle of ICR/IR/BR for series doping are explored. A-C:Cr films with excellent conductivity and anti-corrosive property are acquired. The research discover the oxygen act the dominant impact factor for ICR/IR. Material analyses and resistance test support each other very well.